Effect of the Density of Reactive Sites in P(S‐r‐MMA) Film during Al2O3 Growth by Sequential Infiltration Synthesis. Issue 12 (8th May 2019) - Caligiore, Federica E.; Nazzari, Daniele; Cianci, Elena; Sparnacci, Katia; Laus, Michele; Perego, Michele; Seguini, Gabriele
Abstract: Sequential infiltration synthesis (SIS) consists in a controlled sequence of metal organic precursors and coreactant vapor exposure cycles of polymer films. Two aspects characterize an SIS process: precursor molecule diffusion within the polymer matrix and precursor molecule entrapment into polymer films via chemical reaction. In this paper, SIS process for the alumina synthesis is investigated using trimethylaluminum (TMA) and H2 O in thin films of poly(styrene‐ random ‐methyl methacrylate) (P(S‐ r ‐MMA)) with variable MMA content. The amount of alumina grown in the P(S‐ r ‐MMA) films linearly depends on MMA content. A relatively low concentration of MMA in the copolymer matrix is enough to guarantee the volumetric growth of alumina in the polymer film. In pure polystyrene, metal oxide seeds grow in the subsurface region of the film. In situ dynamic spectroscopic ellipsometry analyses provide quantitative information about TMA diffusivity in pristine P(S‐ r ‐MMA) matrices as a function of MMA fraction, allowing further insight into the process kinetics as a function of the density of reactive sites in the polymer film. This work improves the understanding of infiltration synthesis mechanism and provides a practical approach to potentially expand the library of polymers that can be effectively infiltrated by introducing reactive sites in the polymer chain. Abstract : The amount of alumina grown in the poly(styrene‐ random ‐methyl methacrylate) (P(S‐ r ‐MMA)) films by sequential infiltration synthesis is analyzed by spectroscopic ellipsometry and it depends on MMA content within random copolymer films. A relatively low concentration of MMA in the copolymer matrix is enough to guarantee the volumetric growth of alumina in the polymer film.